1990
DOI: 10.1161/01.cir.82.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful outcome in 130 patients undergoing percutaneous balloon mitral valvotomy.

Abstract: We studied 130 patients undergoing percutaneous balloon mitral valvotomy. The relation between valvular morphology according to a previously described echocardiographic scoring system and hemodynamic outcome expressed as qualitative ("good" and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
12

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(97 citation statements)
references
References 17 publications
4
81
0
12
Order By: Relevance
“…Since MS patients with MVA ≥ 1.5 cm 2 are generally considered to have mild stenosis and are relatively asymptomatic, this value was chosen as the threshold for procedural success. 16 Using this definition, we observed a PMV procedural success rate of 82.4%. Other studies, using the same definition, reported success rates ranging from 70 to 90%.…”
Section: Discussionmentioning
confidence: 91%
“…Since MS patients with MVA ≥ 1.5 cm 2 are generally considered to have mild stenosis and are relatively asymptomatic, this value was chosen as the threshold for procedural success. 16 Using this definition, we observed a PMV procedural success rate of 82.4%. Other studies, using the same definition, reported success rates ranging from 70 to 90%.…”
Section: Discussionmentioning
confidence: 91%
“…This hospital based prospective, non-randomized, observational study included 25 patients of symptomatic severe mitral stenosis [defined as NYHA functional class II-IV, mitral valve area (MVA) of ≤ 1 cm 2 by planimetry, pressure half time (PHT) ≥ 220 msec and/or mean diastolic gradient (MDG) of ≥ 10mm Hg], [10][11][12] in normal sinus rhythm, with suitable valve morphology (defined as Wilkins's score < 8, no or mild mitral regurgitation, and no commissural calcification or LA thrombus) 13,14 who underwent a successful BMV (defined as post-procedural MVA of > 1.5cm 2 or > 50% increase from pre-procedural MVA, and no more than moderate mitral regurgitation after the procedure) at our hospital. 15,16 Exclusion criteria included: i.Documented history or peri-procedural` occurrence of AF or any other sustained arrhythmia.…”
Section: Methodsmentioning
confidence: 99%
“…(8) A score of <9 in association with no more than mild MR, is associated with a good short term outcome following the procedure. (9,10) The following clinical settings are of interest:…”
Section: Patient Selectionmentioning
confidence: 99%